(In)Fertile Male Bodies : Masculinities and Lifestyle Management in Neoliberal Times - Hanna, Esmée Sinéad (Emerald studies in reproduction, culture and society., 2022)
Declining global male fertility rates has generated increased attention on male fertility in recent years. Simultaneously, individualised responsibility for health has been growing. Fertility and lifestyle have therefore become seemingly intertwined. Esmée Sinéad Hanna and Brendan Gough examine men's experiences of fertility and lifestyle practices, exploring personal experiences of the role of lifestyle in the quest for conception as well as the broader promotion of 'lifestyle' within both clinical and online material as a key aspect for 'improving' male fertility. Through the exploration of male fertility and lifestyle factors and their modification we examine the growth of healthism around infertility, the role of neoliberalism within this and how this intersects with masculinity. Using a new notion of liquid masculinity, we explore the fluid nature of societal and personal perspectives on the male infertility experience. In doing so we offer new insights into the now accepted idea that 'sperm' is malleable and that fertility controllable through personal choices, despite their being limited scientific evidence for such claims.